Thomas Aquinas’ definition of the imago Dei and the development of lifelike portraiture - Dominic Olariu (Bulletin du Centre d’Études Médiévales d’Auxerre)
The article examines the philosophical basis of the development of man’s lifelike representation during the 13th century while focusing on Thomas Aquinas’ concept of the « image of man », imago Dei. Aquinas undertakes indeed a profound restructuring of the traditional definition of the imago Dei. By doing so he emphasizes the soul/body relationship in the human being and singles out as profoundly important the soul’s possibility to exercise influence on the body. The article cites passages of Aquinas’ writings to demonstrate the philosopher’s thinking. It also refers to contemporary practices in rituals and hagiographic believes to show the relevance of these ideas outside the strictly philosophical and theoretical sphere. Adopting a new notion of the imago Dei meant in the same breath an increasing of the body’s ennoblement. Its most famous paradigm is the stigmata wonder of Saint Francis of Assisi. As a consequence of the new importance assigned to human corporeity, the bodies of virtuous persons become worth being represented. Lifelike portraiture of the 13th century wishes to underline the extraordinary quality of the shown persons. Therefore the resembling artifacts represent, at their beginnings, the human beings while at the most decisive moment of their earthly life : directly after the death when the body has stopped being influenced by the soul and represents a sort of a relic of the latter.